CONTRACT CHOICE FOR A BRAND-LED HYBRID COMPETING SUPPLY CHAIN CONSIDERING LOYAL CONSUMERS - Zhang, Rong; Li, Huixian; Liu, Bin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
From the perspective of cooperation between brands and manufacturers, this paper constructs a hybrid channel supply chain with brands as the dominant players in the game, considering the different market structure factors of traditional and direct sales channels and introducing channel transfer coefficients and loyal consumers. Based on this model, we compare the optimal solutions of each variable and optimal returns under different decisions and study the wholesale price discount model and revenue compensation coordination mechanism for the hybrid channel. The effectiveness of the coordination mechanism is verified through numerical analysis of the wholesale price discount rate and the revenue compensation coefficient. Moreover, the effect of the parameters on the supply chain’s profitability before and after coordination is also analyzed. The study shows that the smaller the channel transfer coefficient and the larger the demand of loyal consumers is, the more beneficial the increase in the supply chain system’s profitability.